Self-Propelled Motion of an Oil Droplet Containing a Phospholipid and its Stability in Collectivity - Itatani, Masaki; Nabika, Hideki (Frontiers in Physics, 2022)
Collective cell migration (CCM) is a universal process that is responsible for various biological phenomena in living organisms. Therefore, unraveling the mechanism of CCM is critical for understanding the principles underlying such processes and for their application in biomaterials and biomedical science. Among these phenomena, unjamming/jamming transitions are particularly intriguing as they are controlled by three factors: cell motility, cell density, and cell–cell adhesion. However, there is no experimental system to independently demonstrate and control these effects. In this study, we added 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) to a nitrobenzene droplet containing KI and I2 to develop a prototype system that shows self-propelled motion in an aqueous trimethylstearylammonium chloride (TSAC) solution. First, we explored the relationship between the motility of the droplet and experimental parameters, namely, the concentrations of TSAC, I2, and DMPC and droplet size. The droplet showed directional motion driven by Marangoni convection owing to a solubilization promoted by the formation of mixed micelles filled with oil between DMPC and TSA+; notably, droplet motility could be controlled by each parameter. Furthermore, the interfacial tension (γ) at the oil–water interface, measured using the pendant drop method, indicated that each parameter contributed to changes in γ. Based on our experimental results, we inferred that the dynamics of the insertion of TSA+ in the aqueous phase into the self-assembled DMPC membrane covering the nitrobenzene droplet, as well as the solubilization, are important factors that trigger Marangoni convection and lead to controlled droplet motility. Furthermore, the developed droplets remained stable in a confluent state, wherein they were in contact with each other and exhibited various polygonal shapes depending on their size and density because they were protected by a robust self-assembled DMPC membrane layer. The results indicated that the density and the morphology of the droplets are controllable in this system, and that they indirectly altered droplet adhesion. Thus, we procured a prototype system that could be controlled independently using three parameters to elucidate phase transition for CCM. This system can be biomodified through the combination of phospholipids with any biomolecule and can enable a more precise evaluation of the CCM exhibited by living cells.